2020
DOI: 10.14254/1800-5845/2020.16-1.16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating University Academic Efficacy: Institutional Approach

Abstract: The aim of the article is to develop methodological approach to university academic performance evaluation on the basis of instruments of institutional economic theory. The novelty of this work is that unlike other methods authors' method of quantitative evaluation of university academic performance allows for identifying the problems of institutional support of academic activities. During the research authors employed methods of system, logical and economic analysis; empirical information was processed with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is confirmed that the practice-oriented approach in organization of the higher school contributes to developing the entrepreneurial spirit and motivates students to get suitable jobs and find opportunities to implement their business ideas. It positively affects the country's national economy as a whole (Krisnaresanti, 2020;Vlasov et al, 2020;Abdimomynova et al, 2021). Undoubtedly, when opening own business, you may encounter many traditional obstacles, for example, capital limitations and the search for additional investments, business partners and lack of confidence in opening a new business, risks related to the competitors' activities in a particular business environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is confirmed that the practice-oriented approach in organization of the higher school contributes to developing the entrepreneurial spirit and motivates students to get suitable jobs and find opportunities to implement their business ideas. It positively affects the country's national economy as a whole (Krisnaresanti, 2020;Vlasov et al, 2020;Abdimomynova et al, 2021). Undoubtedly, when opening own business, you may encounter many traditional obstacles, for example, capital limitations and the search for additional investments, business partners and lack of confidence in opening a new business, risks related to the competitors' activities in a particular business environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the above-mentioned reasons, a dangerous process of higher education quality reduce is being developed. As a consequence, its inadequacy to the real needs of society becomes obvious, especially in the part of employment (Vlasov et al, 2020). Besides, some researchers prove that higher education does not always lead to greater feeling of own security at the labour market (Lewandowska & Stopa, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%